Environmental, social and governance aspects and financial performance: A symbiotic relationship in Indian manufacturing - Umakanta Gartia; Ajaya Kumar Panda; Apoorva Hegde; Swagatika Nanda (Cleaner Production Letters)
Studying Environmental, Social, and Governance (ESG) aspects and firm performance is crucial for globally understanding how sustainable practices drive long-term profitability and competitiveness in diverse markets. The research gap lies in the need to empirically test the influence of ESG disclosure on corporate performance through the lens of institutional theory and signaling theory. The study aimed to examine the time-variant impact of ESG on the financial performance (FFP) of Indian manufacturing firms from 2019 to 2022. For the study's analysis, we utilized a variant of structural equation modelling called the ‘cross-lagged panel model’. The cross-lagged panel analysis measured the association of aggregate ESG and its dimensions with FFP. Our findings suggested that the investment in the aggregate ESG commitment increased the firms' financial performance among our sample companies. Regarding the individual aspects of ESG, the environmental and societal obligations of the firms had a positive impact on the firms' earnings, whereas the governance aspect harms the FFP. This study provides beneficial recommendations to policymakers, investors, and portfolio managers based on the analysis.